2008
DOI: 10.1002/hlca.200890213
|View full text |Cite
|
Sign up to set email alerts
|

Two New Phenylpropanoid Derivatives from Codonopsis tangshenOliv.

Abstract: Two new 3-hydroxy-3-methylglutaric acid derived phenylpropanoid glucosides, tangshenoside V (1) and tangshenoside VI (2), were isolated from the roots of Codonopsis tangshen Oliv., along with the two known compounds tangshenoside I (3) and tangshenoside III (4). Their structures were elucidated by spectroscopic methods (IR and 1D-and 2D-NMR) and by mass spectrometry (HR-ESI-MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The phenylpropanoids tangshenosides I ( 21 ), II ( 22 ), III ( 23 ) and IV ( 24 ) were first isolated from C. tangshen [ 23 , 25 ]. Tangshenoside V ( 25 ), tangshenoside VI ( 26 ) and codonosides A ( 27 ) and B ( 28 ), considered to be the characteristic components, were isolated from C. tangshen [ 13 , 26 ]. Tangshenoside VI ( 26 ) was also isolated from the aerial parts of C. nervosa [ 27 ].…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…The phenylpropanoids tangshenosides I ( 21 ), II ( 22 ), III ( 23 ) and IV ( 24 ) were first isolated from C. tangshen [ 23 , 25 ]. Tangshenoside V ( 25 ), tangshenoside VI ( 26 ) and codonosides A ( 27 ) and B ( 28 ), considered to be the characteristic components, were isolated from C. tangshen [ 13 , 26 ]. Tangshenoside VI ( 26 ) was also isolated from the aerial parts of C. nervosa [ 27 ].…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…The other components were tentatively identified according to their MS fragmentation pattern, and also by studying their UV spectral characteristics and reported literatures. Accordingly, the peaks were ascribed to cytidine (1) [27,28], uracil (2) [29,30], guanosine (4) [31,32], adenine nucleoside (6) [17,18], syringoside (7) [33,34] (10) [35], isomucronulatol-7,2′-di-O-glucoside (11) [36], biochanin-7-glucoside (12) [37,38], 9,10-dimethoxypterocarpan-3-O-xylosylglucoside (15) [39], 9,10-dimethoxypterocarpan-3-O-β-D-glucoside (16) [39], isomucronulatol-7-O-glucoside (17) [36,40], astragaloside VI (1′) [26,39,41], astragaloside VII (2′) [26,39,41], and astragaloside II (4′) [39,[41][42][43]. However, they still need to be further confirmed with the reference compounds and structural analysis by nuclear magnetic resonance (NMR) method.…”
Section: Identification Of Constituents In Sfi In Fingerprint Chromatmentioning
confidence: 99%
“…in Chinese Pharmacopoeia (Chinese Pharmacopoeia Commission, ). The roots of C. pilosula and C. tangshen as well as Codonopsis Radix have been reported to contain polysaccharides, polyacetylenes, phenylpropanoids, alkaloids and triterpenoids (Wang and Wang, ; Zhu et al ., ; He et al ., ; Song et al ., ; Tsai and Lin, ; Wakana et al ., ). Pharmacological studies have shown that: polyacetylene lobetyolin played a protective role in gastric mucosa injury (Song et al ., ); total saponins from Codonopsis Radix have a protective effect on ischaemia‐reperfusion injury in rats after kidney transplantation (He et al ., ); total alkaloids from Codonopsis Radix caused a significant enhancement of nerve growth factor‐induced neurite outgrowth in PC12 cells as well as an increase of the phosphorylation of mitogen‐activated protein kinase (MAPK) (Liu et al ., ).…”
Section: Introductionmentioning
confidence: 99%